Relationship between glutamate in the limbic system and hypothalamus-pituitary-adrenal axis after middle cerebral artery occlusion in rats - 何明利 陈漫娥 王景周 郭光华 郑衍平 蒋晓江 张猛 (Chinese medical journal, 2003)
Objective To investigate the features of glutamate activity in the limbic system and the effects of glutamate on the activation of the hypothalamus-pituitary-adrenal (HPA) axis throughout both acute cerebral ischemia and reperfusion.Methods The changes in glutamate content in the nervous cell gap, in corticotrophin releasing hormone (CHR) mRNA expression level in brain tissue, and in adrenocorticotropic hormone in blood plasma at different time-points after middle cerebral artery occlusion (MCAO) in rats were determined respectively with high-performance liquid chomatography (HPLC) and in situ hybridization.Results Glutamate content in the hippocampus and the hypothalamus increased rapidly at ischemia 15 minutes, and reached peak value (the averages were 21.05 mg/g ±2. 88 mg/g and 14. 20 mg/g±2.58 mg/g, respectively) at 1 hour after middle cerebral artery occlusion. Dudng recirculation, it retumed rapidly to the baseline level. At 24 hours after reperfusion, it went up once more, and remained at a relative high level until 48 hours after repedusion, and then declined gradually. CRH mRNA expression levels in the temporal cortex, hippocampus and hypothalamus were enhanced markedly at 1 hour ischemia and were maintained until 96 hours after reperfusion. At the same time,adrenocorticotropic hormone level in plasma was relatively increased. In the peak stage of reperfusion injury, there was a significantly positive correlation (n =15, r=0. 566, P<0.05) of the glutamate contents in the hypothalamus with the number of cells positive for CRH mRNA expression level in the hypothalamus.Conclusion It is probable that the CRH system in the central nervous system is mainly distributed in the limbic system, and glutamate might be one of the trigger factors to induce excessive stress response in the HPA axis.